1973
DOI: 10.1107/s0567740873003158
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of rubidium ammonium hydrogen fluorocitrate dihydrate

Abstract: The crystal structure of the racemate of rubidium ammonium hydrogen fluorocitrate dihydrate, RbNHaH(C6HaO7F).2H20, containing the isomer of fluorocitrate that inhibits the enzyme aconitase, has been determined. The configurations of the two isomers in the racemate are I R:2R and 1S:2S for 1-fluoro-2-hydroxy-l,2,3-propanetricarboxylic acid. The crystals are triclinic, space group PT, Z=2, with unit-cell dimensions a=8-458 (2), b= 10.910 (3), c=7.516 (2) A,, 0c= 102.80 ° (3), fl= 115.90 ° (3), 7,=80-50 ° (4). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1975
1975
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…There is only a very small number of crystal structures which display short CF···Rb + contacts. Two of these have biological relevance: Fluorocitrate, whose rubidium−hydrogen−ammonium salt has CF···Rb + contacts of 297.9(5) and 309.5(4) pm (FLUCIT) is highly toxic due to the deactivation of aconitase . Derivatives of the rubidium salt of 5-fluoro-orotate monohydrate [CF···Rb + 288.0, 321.5 pm, RBFORM] are used in cancer treatment …”
Section: Rubidiummentioning
confidence: 99%
“…There is only a very small number of crystal structures which display short CF···Rb + contacts. Two of these have biological relevance: Fluorocitrate, whose rubidium−hydrogen−ammonium salt has CF···Rb + contacts of 297.9(5) and 309.5(4) pm (FLUCIT) is highly toxic due to the deactivation of aconitase . Derivatives of the rubidium salt of 5-fluoro-orotate monohydrate [CF···Rb + 288.0, 321.5 pm, RBFORM] are used in cancer treatment …”
Section: Rubidiummentioning
confidence: 99%
“…From crystallographic data (Carrel and Glusker, 1973) Mn2+ to carbon distances of 2.8-3.2 Á would be expected for carboxylate and carbinol coordination by Mn2+. Hence, the distances of 2.93 and 2.71 Á calculated for the binary complex indicate bidentate coordination or chelation of Mn2+ by both the carboxylate and hydroxyl groups of mandelate (Figure 6).…”
Section: Morganmentioning
confidence: 99%
“…Synthesis of malyl-glutathione thioester by inner membrane vesicles is selectively inhibited by (-)erythrofluoromalate. We have previously identified the biologically active species of the four possible isomers of monofluorocitric acid as (-)erythrofluorocitrate (1, 2); its structure subsequently was confirmed by x-ray crystallography (3,4). Kinetic evidence indicated that (-)erythrofluorocitrate, when preincubated with isolated mitochondria at concentrations of pmol of fluorocitrate per mg of mitochondrial protein, irreversibly inhibited bidirectional citrate transport (5)(6)(7)(8).…”
mentioning
confidence: 99%